Relationship between validity of center of gravity transferring velocities measured by rotary encoder and three-dimensional motion analysis during sit-to-stand movement in the elderly - Yamada, Takayoshi; Demura, Shinichi (International Journal of Health, 2013)
This study examined the validity of center of gravity transferring velocity (VCG) measured by a rotary encoder (RE) during sit-to-stand (STS) movement with that measured by three-dimensional motion analysis (3DMA). Fifteen healthy elderly females (age, 78.7±4.6 years) were asked to stand up as fast as possible without assistance from a chair adjusted for their knee height. VCG was measured simultaneously by 3DMA and RE. The peak and mean velocities from the start to movement completion were calculated by both methods. Cross, crosswise, and vertical directions were also calculated for the 3DMA. Significant relationships were found between peak and mean velocities measured by RE and the cross and vertical velocities measured by the 3DMA (peak velocity: cross, 0.60, vertical, 0.97; mean velocity: cross, 0.77, vertical, 0.75), but low in crosswise (r<0.47). RE is useful for evaluating VCG during STS movement and is highly correlated with the vertical velocity measured by 3DMA.